2013
DOI: 10.1364/boe.4.001332
|View full text |Cite
|
Sign up to set email alerts
|

Real-time, continuous, fluorescence sensing in a freely-moving subject with an implanted hybrid VCSEL/CMOS biosensor

Abstract: Performance improvements in instrumentation for optical imaging have contributed greatly to molecular imaging in living subjects. In order to advance molecular imaging in freely moving, untethered subjects, we designed a miniature vertical-cavity surface-emitting laser (VCSEL)-based biosensor measuring 1cm 3 and weighing 0.7g that accurately detects both fluorophore and tumor-targeted molecular probes in small animals. We integrated a critical enabling component, a complementary metal-oxide semiconductor (CMOS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
(28 reference statements)
0
15
0
Order By: Relevance
“…O’Sullivan et al (O’Sullivan et al 2013) reported the fabrication of a miniature, integrated semiconductor-based fluorescence sensor, designed for detecting fluorophores and tumor-targeted molecular probes (Fig. 2f).…”
Section: Miniaturized Optical Systems Based On Exogenous Contrast Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…O’Sullivan et al (O’Sullivan et al 2013) reported the fabrication of a miniature, integrated semiconductor-based fluorescence sensor, designed for detecting fluorophores and tumor-targeted molecular probes (Fig. 2f).…”
Section: Miniaturized Optical Systems Based On Exogenous Contrast Agentsmentioning
confidence: 99%
“…When the system was tested on freely moving mice, the authors reported an increase of ~ 500 pA in the photocurrent following injection of Cy 5.5 fluorescence dye. This miniaturized system required precise positioning and fixation to the targeted object, which made it difficult to use on soft tissue or when imaging small targets (O’Sullivan et al 2013). …”
Section: Miniaturized Optical Systems Based On Exogenous Contrast Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, molecular diagnostic is a costly procedure. A research report previously demonstrated the capability of CMOS sensor-based molecular diagnostics [28,35,94]. Indeed, CMOS sensors constitute a suitable device for POC applications due to their availability in mobile phone cameras and user-friendliness.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…In particular, narrowband photodetection in the far‐red range (i.e., photodetectors with peak response at 700–750 nm)—dimly visible to the human eye and at the same time distinct from the infrared region—is of considerable interest, in view of its role in many natural processes and technological applications. Narrowband photodetection in the far‐red range is relevant to analytical biology (e.g., flow cytometry32), medical diagnostics (e.g., brain imaging,33 in‐vivo tumor detection34), remote sensing,35 botany,36 precision agriculture,37 and food quality inspection 38. It is important to note that a large number of such applications require spectral widths loosely around 100 nm, in principle within reach of the NBA approach—while ultranarrowband passbands (spectral with ≲50 nm) would lead to poor photon collection, hence would be unsuitable for the purpose.…”
Section: Introductionmentioning
confidence: 99%